2021
DOI: 10.1021/acsami.0c22587
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-poly (β-Amino Ester) Nanoparticles Are a Generalizable Strategy for High Loading and Sustained Release of HDAC Inhibitors

Abstract: Therapeutic development of histone deacetylase inhibitors (HDACi) has been hampered by a number of barriers to drug delivery, including poor solubility and inadequate tissue penetration. Nanoparticle encapsulation could be one approach to improve the delivery of HDACi to target tissues; however, effective and generalizable loading of HDACi within nanoparticle systems remains a long-term challenge. We hypothesized that the common terminally ionizable moiety on many HDACi molecules could be capitalized upon for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…A similar effect was observed by our group with alginate nanocarriers, which increased the MIC of miltefosine . Other authors reported comparable effects of prolonged/controlled release systems, such as polymeric and calcium phosphate nanoparticles and liposomes, attributing increases of IC 50 value to the reduced availability of the encapsulated drug. Based on the in vitro release results, we estimate that free drug levels at 72 h should be approximately 15% of the total drug amount. Thus, if we consider that it is the free portion of the drug that will be available to exert cell effects, IC 50 values would be lower.…”
Section: Discussionsupporting
confidence: 80%
“…A similar effect was observed by our group with alginate nanocarriers, which increased the MIC of miltefosine . Other authors reported comparable effects of prolonged/controlled release systems, such as polymeric and calcium phosphate nanoparticles and liposomes, attributing increases of IC 50 value to the reduced availability of the encapsulated drug. Based on the in vitro release results, we estimate that free drug levels at 72 h should be approximately 15% of the total drug amount. Thus, if we consider that it is the free portion of the drug that will be available to exert cell effects, IC 50 values would be lower.…”
Section: Discussionsupporting
confidence: 80%
“…To date most of the research activity in the field has been focused on efforts of encapsulating quisinostat into various drug carriers. To that end, various macromolecular systems have been explored, such as nanoparticles on the basis of poly(lactide)-blockpoly(ethylene glycol) [15], poly (lactide-co-glycolide)-lecithin-poly(ethylene glycol) [6], and polysaccharide [16], as well as matrices composed of β-cyclodextrin-poly (β-amino ester) networks [17] and bioerodible radiopaque hydrogels [14]. Despite offering multiple distinct advantages, all of these methods usually involve sophisticated chemical and formulation approaches and require multi-step production processes.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic agents are plagued by poor water solubility, rapid clearance, and poor tissue distribution. [91] Given that the greater permeability of tumor vessels than normal vessels and the impaired lymphatic flow, nanomedicines accumulate preferentially in tumor tissue and remain for a long time, which is called the enhanced permeability and retention (EPR) effect. [92] Nanomedicine delivery strategies can utilize EPR effectmediated passive targeting or ligand-mediated active targeting to deliver nanomedicines to tumor tissue after systemic delivery.…”
Section: Epigenetic Modulator-based Nanotechnology For Improving Tumo...mentioning
confidence: 99%